2013
DOI: 10.1038/srep01941
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic radiative lifetime derived via absorption cross section of one-dimensional excitons

Abstract: Intrinsic radiative lifetime is an essential physical property of low-dimensional excitons that represents their optical transition rate and wavefunction, which directly measures the probability of finding an electron and a hole at the same position in an exciton. However, the conventional method that is used to determine this property via measuring the temperature-dependent photoluminescence (PL) decay time involves uncertainty due to various extrinsic contributions at high temperatures. Here, we propose an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…To discuss whether the excited states are delocalized or localized over the [n]CPPs, we assumed that the excitons can move in a circumferential direction along the [n]CPPs. For free excitons in 1D systems, the radiative recombination rate of an exciton is proportional to the oscillator strength f x , which for a 1D structure is expressed by [24][25][26][27]…”
Section: Resultsmentioning
confidence: 99%
“…To discuss whether the excited states are delocalized or localized over the [n]CPPs, we assumed that the excitons can move in a circumferential direction along the [n]CPPs. For free excitons in 1D systems, the radiative recombination rate of an exciton is proportional to the oscillator strength f x , which for a 1D structure is expressed by [24][25][26][27]…”
Section: Resultsmentioning
confidence: 99%
“…Однако отсутствие устойчивого формализма часто приводит к неоднозначности в трактовке экспериментальных результатов. В этом случае принципиальное значение приобретает качество обработки экспериментальных зависимостей кинетики люминесценции [13][14][15][16][17]. Целью исследования настоящей работы являлось изучение кинетики фотолюминесценции (ФЛ) гибридной полупроводниковой наноструктуры, представляющей собой массив ННК InP/InAsP/InP, сформированных методом молекулярно-пучковой эпитаксии на подложке Si(III), путём аппроксимации экспериментальных кинетических зависимостей несколькими математическими моделями.…”
Section: Introductionunclassified
“…In 2013, it was shown that the radiative decay of an exciton can efficiently display the intrinsic physical property of a low-dimensional semiconductor, while the extrinsic disturbances hardly contribute to the properties of the exciton [ 19 , 20 , 21 , 22 ]. Moreover, various details with respect to the intrinsic physical property—such as decay time—can be extracted from the exciton decay in conjugated polymers [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%